Evaluasi Tingkat Kepuasan Pengguna Fasilitas Jembatan Penyeberangan Orang (JPO) Jalan Jaksa Agung Suprapto Kota Malang - Renggi Tay, Roylisandro; Primasworo , Rifky Aldila; Rahma , Pamela Dinar (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2024)
The rights and responsibilities of pedestrians are regulated by legislation as the government priorities their safety, security and convenience. Pedestrians are entitled to the provision of supporting facilities such as road surfaces, crossings, and other facilities in accordance with Article 131 of Law No. 22 of 2009 concerning Road Traffic and Transport. The Pedestrian Bridge (JPO) is made with the aim that circulation in traffic does not interfere with other transportation, so that the path to the specified destination can run smoothly. The result of the satisfaction level is 61.20%, which means that the level of satisfaction and the level of importance of the facilities that have been provided by the management of the pedestrian bridge is satisfactory / good. Of the 13 attributes of the questionnaire, there are 3 attributes that are included in quadrant I (top priority), these attributes are very important but their performance is not satisfactory. Efforts to increase the satisfaction of users of the pedestrian bridge (JPO) Jalan Jaksa Agung in Malang City are in the position of quadrant I space B, namely Stable Growth Strategy / stable growth strategy. These results indicate that there is a need for a strategy to maintain existing growth by increasing strengths and taking advantage of opportunities to achieve the expected quality of facilities so that the condition of the JPO building improves to make it easier for users.